The impact of safety culture dimensions on workplace accidents: an application in the Moroccan automotive industry - Mouna Salhi; Youness Chater; Amal Maurady (International Journal of Occupational Safety and Health, 2024)
Introduction: There is a general accord that safety culture is multidimensional. but limited research and publications are there about those dimensions. Almost one-third of the publications presenting safety culture definitions do not discuss the safety culture dimension nor the relationship between the safety culture dimensions and workplace accidents.  To further understand the factors influencing this correlation. it appeared appropriate in this situation to investigate the relationship between the safety culture dimensions and occupational accidents. This study aims to identify the safety culture dimensions in the automotive industry in Morocco and its relations with occupational accidents.